Storm surge - Gutteridge, Rene (Tyndale House Publishers, 2005)
FBI agent Mick Kline is forced to work with Libby Lancaster on his latest case and as he searches for the truth about a ten year old murder case, his feelings for his new partner grow more complex and threaten the case.